A CONTEMPORARY VIEW ON CHALLENGING ISSUES IN ENDODONTICS (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Recommendations for superior endodontic dental therapy are offered. Issues in endodontics are emphasized. A contemporary viewpoint on the concepts and phases of endodontic coronal and root preparation is provided. Recommendations are provided for mistake avoidance and the attainment of high-quality endodontic therapy.